TMAO: how gut microbiota contributes to heart failure - Zhang, Yixin; Wang, Yuan; Ke, Bingbing; Du, Jie (Translational research : the journal of laboratory and clinical medicine, 2021)
An increasing amount of evidence reveals that the gut microbiota is involved in the pathogenesis and progression of various cardiovascular diseases. In patients with heart failure (HF), splanchnic hypoperfusion causes ischemia and intestinal edema, allowing bacterial translocation and bacterial metabolites to enter the blood circulation via an impaired intestinal barrier. This results in local and systemic inflammatory responses. Gut microbe-derived metabolites are implicated in the pathology of multiple diseases, including HF. These landmark findings suggest that gut microbiota influences the host's metabolic health, either directly or indirectly by producing several metabolites. In this review, we mainly discuss a newly identified gut microbiota-dependent metabolite, trimethylamine N-oxide (TMAO), which appears to participate in the pathologic processes of HF and can serve as an early warning marker to identify individuals who are at the risk of disease progression. We also discuss the potential of the gut–TMAO–HF axis as a new target for HF treatment and highlight the current controversies and potentially new and exciting directions for future research.